Functions of Uninflatable in the Drosophila melanogaster wing and notum - Taylor Zhang; Juliet E. Jones; Laura J. Yee; Sebastian C. Sy; Monika Karki; Manshi Patel; Seniha Elcik; Kathleen M. Beckingham (PLoS ONE, 2026)
The Drosophila gene uninflatable ( uif ) encodes a conserved insect protein, first identified for its roles in the development and endopolyploid growth of several larval tissues. Uif is a transmembrane protein and its large extracellular domain contains several protein-protein interaction motifs, including multiple EGF ( E pidermal G rowth F actor-like) repeats. More recent studies have established that Uif can interact with Notch, a major regulator of Drosophila growth and differentiation, through its EGF repeats and have identified ways that Uif binding can modify Notch behavior. Endocytosis of Notch-Uif complexes into a particular class of endosomes has also been identified and implicated in cell fate decisions in the sense organs of the notum (thorax). We have examined uif’s functions in the Drosophila wing to assess possible roles in 1) growth of a mitotically derived tissue, 2) cell fate decisions in specialized wing structures, and 3) Notch -dependent processes. We used previously characterized Gal4 lines and RNAi constructs to suppress uif and Notch in different wing compartments. In addition to a role in mitotic growth throughout the wing, we have identified two new uif activities that are also shared with Notch : 1) regulation of pigment synthesis within the wing cuticle and 2) control of chemosensory sense organ number in the anterior wing margin through a role in an apoptosis-related mechanism. However, uif does not participate in two roles of Notch that regulate cell fate decisions: sense organ differentiation and formation of wing vein tissue. Given the similarities in the development of the notal and wing margin sense organs, we investigated further the previously proposed role for uif in differentiation of these structures on the notum. We found that loss of uif affects the growth of the bristles of the notal microchaete sense organs, but not their differentiation.